Earnings of Academic Scientists and Engineers: Intersectionality of Gender and Race/Ethnicity Effects. (May 2018) - Tao, Yu
While research increasingly examines the intersection of gender and race/ethnicity in science and engineering, not much is known regarding how they work together to affect career outcomes. This article examines gender earnings gaps among academic scientists and engineers by race/ethnicity. Using data from National Science Foundation's Survey of Doctorate Recipients (2003, 2006, 2008, 2010, and 2013), I find that White women earned less than their male counterparts in 2003 and 2006, but the earnings gap closed over time. African American women did not earn less than their male counterparts in any year. Asian American women earned less only in 2013 (due to the high income of Asian American men), and Hispanic women earned less only in 2010 (due to their low income relative to other groups). The findings of relative improvement in gender earnings equality are analyzed in the context of disadvantages women face in other aspects of their careers.